The work of hospitals : global medicine in local cultures - Olsen, William C.; Sargent, Carolyn F., 1947- (Rutgers University Press, 2022)
In the context of neoliberalism and global austerity measures, health care institutions around the world confront numerous challenges in attempting to meet the needs of local populations. Examples from Africa (including, Ethiopia, Ghana, and Congo), Latin America (Peru, Mexico, Guatemala), Western Europe (France, Greece), and the United States illustrate how hospitals play a significant role in the social production of health and disease in the communities where they are. Many low-resource countries have experienced increasing privatization and dysfunction of public sector institutions such as hospitals, and growing withdrawal of funding for non-profit organizations. Underlying the chapters in The Work of Hospitals is a fundamental question: how do hospitals function lacking the medications, equipment and technologies, and personnel normally assumed to be necessary? This collection of ethnographies demonstrates how hospital administrators, clinicians, and other staff in hospitals around the world confront innumerable risks in their commitment to deliver health care, including civil unrest, widespread poverty, endemic and epidemic disease, and supply chain instability. Ultimately, The Work of Hospitals documents a vast gulf between the idealized mission of the hospital and the implementation of this mission in everyday practice. Hospitals thus become "contested space" between policy and practice